Design of Mathematics Learning Media based on Discovery Learning to Improve Problem Solving Ability - Epa Wira Darmawan; Suparman Suparman (Universitas Muhammadiyah Surakarta, 2019)
Problem-solving is one of the 21st century skills and is included in the 2013 curriculum. Students with low problem-solving abilities will have difficulty completing math problems that require high-level thinking. Learning media that does not contain problem-solving skills will hinder the achievement of student competence. This research has two objectives. The first objective is to analyze the needs of learning media that are in accordance with student characteristics, curriculum, learning models and teacher readiness. The second objective is to design discovery learning based learning media to improve students' problem-solving abilities. This research uses design research method with type of development studies. The research subjects consisted of teachers and students. Data collection instruments used interview guidelines, observation guidelines, and questionnaires. Interview guides to get information from teachers and students regarding the readiness of teachers in applying the 2013 curriculum and learning difficulties in mathematics. Observation guidelines are used to obtain information about student learning characteristics. The questionnaire was used to get the needs of mathematics learning media. The data were analyzed using qualitative descriptive. Research provides several results. First, most students consider learning less attractive. Second, the 2013 curriculum cannot be fully implemented in the classroom. Third, discovery learning models can improve problem-solving skills. Fourth, the design of discovery learning based learning media. This study concludesthat discovery learning based media to improve problem-solving skills needs to be developed